Between past and present: ancient shipwrecks and the contemporary migration issue. An ethnoarchaeological approach over the Mediterranean - Aga Pereira Passos, Letícia (Romanitas - Revista de Estudos Grecolatinos, 2025)
This paper aims to establish an overview comprising Mediterranean Archaeology and Ethnoarchaeology to discuss themes such as migration, memory, and temporality. The study of contemporary societies and their relationship with the material world can help to understand the intersections between the past and the present of societies that lived in the same geographical space of the Mediterranean. Thus, we will explore the navigation scenario, focusing on shipwrecks. Although such phenomena occur for different reasons, they are felt and expressed by distinct societies, offering archaeological interpretations of the past, while also serving as a possibility of archaeology of the present.